Penentuan Sisa Umur Pakai Struktur Conveyor H pada Tambang Batubara PT GHI di Kabupaten Tapin, Provinsi Kalimantan Selatan - Soultan Taufiq; Elfida Moralista; Iswandaru (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyor structure is a tool that is applied to the mining industry as a tool that supports the process of moving excavated materials such as coal. The structure of the conveyor is made of steel which is subject to corrosion. The disadvantage of corrosion is that it results in a reduction in the thickness of the conveyor structure. Therefore, it is necessary to control and monitor corrosion on the conveyor structure to be observed, so that corrosion can be controlled. The purpose of this research is to determine the type of corrosion, corrosion rate, remaining service life, and control methods. The methodology used in this study is measuring the thickness reduction of the conveyor structure. This research was conducted on a conveyor structure of 90 meters above ground level. Measurement of the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130 at 25 observation points. The environmental conditions in the research area are the air temperature in the range of 26 oC-32oC, while the rainfall with an average range of 197.58 mm-165.71 cm. In controlling this corrosion using a coating method with Seaguard 5000 primer coating, Sherglass FF intermediate coating, and aliphatic acrylic modified polyurethane top coating. The corrosion rate of the conveyor structure ranges from 0.18-0.3 mm/year. The remaining service life of the conveyor structure ranges from 7,16-9,65 years. The service life of the conveyor structure is 7 years, while the design life is 15 years. 25 observation points, 28.00% below the design life. Abstrak. Conveyor adalah alat yang diaplikasikan pada industri pertambangan sebagai alat yang menunjang dalam proses pemindahan material bahan galian contohnya batubara. Struktur conveyor terbuat dari baja yang dapat mengalami korosi. Kerugian terjadinya korosi yaitu mengakibatkan pengurangan ketebalan struktur conveyor. Oleh karena itu, diperlukannya pengendalian serta monitoring korosi pada struktur conveyor yang akan diamati, sehingga korosi dapat dikendalikan. Tujuan dilakukannya penelitian ini adalah untuk mengetahui jenis korosi, laju korosi, sisa umur pakai, dan metoda pengendaliannya. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran pengurangan ketebalan struktur conveyor. Penelitian ini dilakukan pada struktur conveyor sepanjang 90 meter yang berada di atas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130 pada 25 test point. Kondisi lingkungan di daerah penelitian yaitu temperatur udara kisaran 26 oC-32oC, sedangkan curah hujan dengan rata-rata kisaran 197,58 mm-165,71 cm. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Dalam pengendalian korosi ini menggunakan metoda coating dengan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating aliphatic acrylic modified polyurethane. Laju korosi struktur conveyor berkisar antara 0,18-0,3 mm/tahun. Sedangkan sisa umur pakai struktur conveyor berkisar antara 7,16-9,65 tahun. Umur pakai struktur conveyor yaitu 7 tahun, sedangkan umur desainnya 15 tahun. Pada 25 test point, didapatkan persentase sebesar 28,00% yang diprediksikan di bawah umur desainnya.